Pendampingan Pengolahan Sediaan Wedang Telang (Clitoria ternatea L.) pada Masyarakat Landasan Ulin Utara, Banjarbaru - Fitriyanti Fitriyanti; , Karunita Ika Astuti (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Clitoria ternatae has many health benefits, one of which is to increase body immunity. As a flower that is easy to find and grows in various regions, this is one of the plants that can be used as a health drink in the form of wedang. This community service aims to provide knowledge and skills in making wedang with the main ingredients from nature. The training materials (theory and practice) were place at the houses of RT.07, RW.01 in the Landasan Ulin Village, Liang Anggang District, Banjarbaru. Apart from being aimed at providing education to local residents regarding the benefits of the butterfly pea flower, they are also educated on how to cultivate it, how to use it and how to pack it. So that later the local residents/communities can carry out the processing in an independent manner independently both for personal consumption and used as business.